Does crowd support drive the home advantage in professional soccer? Evidence from German ghost games during the COVID-19 pandemic - Kai Fischer; Justus Haucap (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
This paper examines the relation between crowd support and home advantage in professional soccer. For that purpose, we make use of a unique "natural experiment": so-called ghost games in the three top divisions of German professional soccer during the Corona pandemic. We find that there is a reduced home advantage in the first division, whereas no change can be observed in the second and third division. Our regression analysis indicates that the decrease in the home advantage and the different effects across the three divisions are not sensitive to a variety of performance, location, and team covariates and most suitably explained by the lower occupancy rate in the stadia. Hence, the decrease in the occupancy rates to zero at the ghost games has been less dramatic for teams that have been used to low occupancy rates. Put differently, the more a team has been used to a full stadium, the more severe is the loss of home advantage. The ghost game effect decreases over time, however, implying that players adapt and get used to the new situation. Our analysis also sheds light on potential drivers of home advantage such as stadium tracks, travel distance, derbies and within-week matches.
Keywords: Z20; Z21; 330; Home Advantage; Corona Pandemic; Professional Soccer; Stadium Occupancy